Pemanfaatan Hasil Tangkapan Ikan Dengan Pelatihan Pembuatan Sossis Ikan Di Desa Bilungala Kecamatan Bonepantai Kabupaten Bone Bolango - Mustaqimah, Nur; Usman, Nurul Fajryani; Pagalla, Devi Bunga; Nurhayati, Nurhayati (Universitas Negeri Gorontalo, 2023)
One of the areas in Gorontalo Province that has fishery potential from Tomini Bay is Bilungala Village, where the most commonly caught fish is Cakalang (Katsuwonus pelamis). Cakalang has a fairly high economic value and is much preferred because it has good meat density, especially to be used as a source of protein. But so far, the community does not have much knowledge about the management of Cakalang, which is the main catch. One of the processed products that can be made with Cakalang is fish sausage. Sausage is a food product that has nutritional value and meets the needs of the body. This processed product is also more practical to serve. The resulting product can also be an alternative business to improve the community's economy. Therefore, a fish processing training activity was carried out in the form of cakalang fish sausage. The aim of this training is to equip housewives in the village with skills in processing fish catches into nutritious and durable food products. The location of this community service activity was carried out in Bilungala Village, Bonepantai District, Bone Bolango Regency. The target is housewives in the village. The activity was carried out on November which consisted of the preparation stage by conducting a survey and the implementation stage by conducting training with direct demonstrations and together with the participants making the product. This activity went smoothly. Participants were very enthusiastic about participating in the activity from the beginning of the activity to the end of the activity. This activity requires follow-up in the form of marketing training for processed fish products in the form of fish sausage. The training can be an asset for participants consisting of housewives to market their products which in the end are able to increase their income and help the community's economy.